2008
DOI: 10.1111/j.1538-7836.2008.03059.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and persistence of warfarin or aspirin in patients with chronic atrial fibrillation in general practice: do the appropriate patients receive stroke prophylaxis?

Abstract: To cite this article: Gallagher AM, Rietbrock S, Plumb J, van Staa TP. Initiation and persistence of warfarin or aspirin in patients with chronic atrial fibrillation in general practice: do the appropriate patients receive stroke prophylaxis? J Thromb Haemost 2008; 6: 1500-6. Summary. Background: Practice guidelines recommend longterm stroke prophylaxis in patients with chronic atrial fibrillation (cAF). Objectives: To examine treatment initiation and persistence and factors that influence the choice of cAF tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
3
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(171 citation statements)
references
References 31 publications
12
143
3
13
Order By: Relevance
“…Overall, this study suggested that less than half (49.3%) of patients with a history of AF received an anticoagulant and that anticoagulant uptake increases through CHADS 2 score 0-3 and thereafter reaches a plateau [16]. These results are similar to those of another recent study [12] and represent an improvement compared to what had previously been described [32]. Nevertheless, if the treatment threshold for anticoagulation is a CHADS 2 score P1, this would include 84% of the AF population, which is significantly higher than the percentage of patients currently given anticoagulation.…”
Section: Review Articlesupporting
confidence: 81%
“…Overall, this study suggested that less than half (49.3%) of patients with a history of AF received an anticoagulant and that anticoagulant uptake increases through CHADS 2 score 0-3 and thereafter reaches a plateau [16]. These results are similar to those of another recent study [12] and represent an improvement compared to what had previously been described [32]. Nevertheless, if the treatment threshold for anticoagulation is a CHADS 2 score P1, this would include 84% of the AF population, which is significantly higher than the percentage of patients currently given anticoagulation.…”
Section: Review Articlesupporting
confidence: 81%
“…6,7,18 Cowan et al report that 36.2% received antiplatelets alone; 5 suggesting that the prescription of antiplatelet therapy for stroke prevention in AF may vary markedly in the UK. The discrepancy in the proportions of patients receiving antiplatelet therapy between the present study and Cowan et al …”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…These findings are similar to the results from two recent analyses of UK general practice 5,10 and a global survey of OAC, 6 but contrast with previous analyses of antithrombotic therapy by stroke risk. 17,18 This could suggest that the greater emphasis on risk stratifying patients advocated by guidelines is beginning to affect contemporary clinical practice, and that using the GRASP-AF tool, incorporating the CHA 2 DS 2 -VASc score, could help to identify those at risk of stroke and increase the use of appropriate OAC therapy.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] The authors were interested not only in the patterns of risk and levels of anticoagulant use, but also in the ability of primary care data to support risk estimation. A software tool (GRASP-AFGuidance on Risk Assessment and Stroke Prevention in Atrial Fibrillation) has been developed for UK general practices, 17 which produces lists of high-risk but untreated individuals.…”
Section: Introductionmentioning
confidence: 99%